Narratives of Tradition and Modernity: How Lampung Tapis Gains International Attention (Case Study: Tapis Lampung) - Prita Masyithah Khairunnisa; Sirli Anillah; Eka Nisatul Mukaroh; Faby Saktioriza Nugraha; Rafif Subana Aqdun Bilqolbi; Agrianti Komalasari; Sudrajat (PT. Altaf Publishing Corp, 2025)
Tapis Lampung is a cultural heritage textile that carries significant historical, aesthetic, and philosophical value and holds strong potential for development within the global creative industry. However, existing studies have largely focused on the symbolic, artistic, and preservation aspects of Tapis Lampung, with limited empirical attention given to its introduction in international professional or corporate settings and its role in fostering cross-cultural understanding. Addressing this gap, this study aims to introduce Tapis Lampung to an international audience and examine its impact on cross-cultural engagement through a presentation conducted during the Global Accounting Issues Seminar at Baiwang Co., Ltd., China. The method employed involved an interactive presentation that combined visual materials, cultural narratives, and direct examination of authentic Tapis fabrics. The results indicate that participants demonstrated increased cultural awareness and appreciation of Lampung’s values, particularly regarding the symbolic meanings and craftsmanship embedded in Tapis. These findings support existing literature asserting that traditional crafts can achieve global relevance when supported by cultural storytelling and strategic presentation. Furthermore, the activity contributed to Indonesia’s cultural diplomacy by facilitating cross-cultural dialogue and generating interest in potential international collaboration within cultural initiatives and creative economy development. Overall, this study highlights the effectiveness of narrative–visual approaches in promoting traditional cultural products globally and reinforces the positioning of Tapis Lampung as a competitive cultural and economic asset in international contexts.